Design and implementation hamming neural network with VHDL - Liqaa Saadi Mezher (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
Hamming Neural Network is type of artificial neural network consist of two types of layers (feed forward layers and recurrent layer). In this paper, two inputs of patterns in bianary number were used. In the first layer, two neurons and pure line function were used. In the second layer, three neurons and positive line function were used. Also applied Hamming Neural networks algorithm in three simulation methods (logical gate method, software program coding method and instant block diagram method). In this work in VHDL software program was used and FPGA hardware used.